2020
DOI: 10.3389/fonc.2020.574383
|View full text |Cite
|
Sign up to set email alerts
|

Silencing SAPCD2 Represses Proliferation and Lung Metastasis of Fibrosarcoma by Activating Hippo Signaling Pathway

Abstract: The primary problem associated with fibrosarcoma is its high potential to metastasize to the lung. Aberrant expression of SAPCD2 has been widely reported to be implicated in the progression and metastasis in multiple cancer types. However, the clinical significance and biological roles of SAPCD2 in fibrosarcoma remain unknown. Here, we reported that SAPCD2 expression was markedly elevated in fibrosarcoma tissues, and its expression was differentially upregulated in fibrosarcoma cell lines compared with that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The transition from high expression levels of E-cadherin to low expression levels of N-cadherin are trademarks of aggressive tumor growth and stimulates initiation of the EMT, a key process during the initiation of tumor metastasis. Zhu et al additionally identified SAPCD2 overexpression being significantly correlated with metastasis in fibrosarcoma patients and demonstrated that SAPCD2 knockdown attenuated lung metastasis in vivo by activating the Hippo signaling pathway as described above [33]. Together, the above reports illustrate the ability of SAPCD2 to influence the main metastatic signaling cascades.…”
Section: The Role Of Sapcd2 In Tumor Metastasis and The Underlying Me...mentioning
confidence: 70%
See 2 more Smart Citations
“…The transition from high expression levels of E-cadherin to low expression levels of N-cadherin are trademarks of aggressive tumor growth and stimulates initiation of the EMT, a key process during the initiation of tumor metastasis. Zhu et al additionally identified SAPCD2 overexpression being significantly correlated with metastasis in fibrosarcoma patients and demonstrated that SAPCD2 knockdown attenuated lung metastasis in vivo by activating the Hippo signaling pathway as described above [33]. Together, the above reports illustrate the ability of SAPCD2 to influence the main metastatic signaling cascades.…”
Section: The Role Of Sapcd2 In Tumor Metastasis and The Underlying Me...mentioning
confidence: 70%
“…The expression of SAPCD2 in fibrosarcoma was demonstrated for the first time by Zhu et al [33]. Fibrosarcoma is a highly malignant cancer of mesenchymal origin with a high potential to metastasize to the lung.…”
Section: Sapcd2 In Other Cancer Typesmentioning
confidence: 96%
See 1 more Smart Citation
“…For the first time, we showed that oncogenes like FAM83D, SAPCD2 were downregulated upon curcumin treatment in all three cells, and TSGs like ZNF292, 77 NKAPL, and CCL21 were upregulated in breast cancer cell lines. FAM83D 78–80 and SAPCD2 81 are known to promote tumorigenesis, induce drug resistance and promote invasiveness. FAM83D promotes cell proliferation and motility by downregulating TSG FBXW7 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have shown an elevated expression level of SAPCD2 in a number of human cancers, such as colorectal cancer, fibrosarcoma, melanoma, and non-small cell lung cancer. SAPCD2 largely functions as an oncogene playing important roles in tumorigenesis by promoting cell proliferation, cell migration, and invasion by various pathways, such as PI3K/Akt activation, MAPK activation, or Hippo signaling suppression [ 10 13 ]. A recent study, however, suggested that SAPCD2 blocks Wnt/β-catenin signaling by interaction with Axin1 and in some contexts might function as a tumor suppressor [ 14 ].…”
Section: Introductionmentioning
confidence: 99%